The Effect of Design on User Comfort in the Dseign of Rest Areas and Service Facilities in Kulon Progo Regency - Dini Setiyowati; Tigor Wilfritz Soaduon Panjaitan (Kirana Publisher (KNPub), 2026)
High vehicle mobility in 2025 has contributed to an increase in accident rates, with human factors being the dominant cause at 94.7%. Driver fatigue often remains unaddressed because existing Rest and Service Areas (TIP) tend to only provide physical facilities rather than mental recovery. This qualitative study aims to formulate a TIP concept that addresses the psychological needs of toll road users through a biophilic architecture approach. Through literature studies and evaluations of similar facilities, the